2021
DOI: 10.1021/acs.orglett.1c04189
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 3-Orsellinoxypropanoic Acid in Penicillum crustosum is Catalyzed by a Bifunctional Nonreducing Polyketide Synthase

Abstract: The heterologous expression of a nonreducing polyketide synthase gene oesA from Penicillium crustosum led to the identification of orsellinoylpropanoic acid (1). Domain deletion and recombination proved that OesA catalyzes not only the formation of orsellinic acid but also its transfer to 3-hydroxypropanoic acid. Both ACP domains contribute independently and complementarily to the product formation. Feeding experiments provided evidence that only the orsellinyl residue is derived from acetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…18,26 Recently, Xiang et al reported that the OseA-TE domain catalyzes the ester bond formation of ACP-bound 2 with 3hydroxypropionic acid in vivo (Figure S3); 27 however, the OseA-TE domain cannot catalyze the dimerization of ACPbound 2, possibly due to its low sequence identity (∼27%) to the AN7909-TE domain. 27 Therefore, this provides an opportunity to investigate the conserved catalytic residues of AN7909-TE domain involved in Smiles rearrangement. Sequence alignments among the AN7909-TE domain (with its homologous enzymes), OseA-TE domain, and other welldocumented fungal nrPKS TE domains showed that many amino acid residues are conserved in the AN7909-TE domain (Figure S4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18,26 Recently, Xiang et al reported that the OseA-TE domain catalyzes the ester bond formation of ACP-bound 2 with 3hydroxypropionic acid in vivo (Figure S3); 27 however, the OseA-TE domain cannot catalyze the dimerization of ACPbound 2, possibly due to its low sequence identity (∼27%) to the AN7909-TE domain. 27 Therefore, this provides an opportunity to investigate the conserved catalytic residues of AN7909-TE domain involved in Smiles rearrangement. Sequence alignments among the AN7909-TE domain (with its homologous enzymes), OseA-TE domain, and other welldocumented fungal nrPKS TE domains showed that many amino acid residues are conserved in the AN7909-TE domain (Figure S4).…”
mentioning
confidence: 99%
“…Recently, Xiang et al reported that the OseA-TE domain catalyzes the ester bond formation of ACP-bound 2 with 3-hydroxypropionic acid in vivo (Figure S3); however, the OseA-TE domain cannot catalyze the dimerization of ACP-bound 2 , possibly due to its low sequence identity (∼27%) to the AN7909-TE domain . Therefore, this provides an opportunity to investigate the conserved catalytic residues of AN7909-TE domain involved in Smiles rearrangement.…”
mentioning
confidence: 99%
“…28,29 Li et al reported that the TE domain of OesA catalyzed the ester bond formation of ACP-bound 3 with 3-hydroxypropionic acid. 30 However, the TE domain of MollE for the biosynthesis of mollicellin Z (9) was found to have strict substrate specificity for dimers, as such to warrant the effective production of the dimer precursor depside for subsequent postmodifications. These results suggested that the TE domain of NR-PKS from fungi plays an important role for structural diversity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For examples, Zhou et al reported that the TE domain of AN7909 (OrsA) was multifunctional to catalyze not only the production of a monomer orsellinic acid ( 3 ) but also the formation of the ester bond and a diaryl ether linkage (Figure S1). , Li et al reported that the TE domain of OesA catalyzed the ester bond formation of ACP-bound 3 with 3-hydroxypropionic acid . However, the TE domain of MollE for the biosynthesis of mollicellin Z ( 9 ) was found to have strict substrate specificity for dimers, as such to warrant the effective production of the dimer precursor depside for subsequent postmodifications.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work with P. crustosum PRB-2 revealed that only a few of these gene clusters, such as those of peniphenones, penilactones, and their precursors, are expressed under laboratory conditions [ 11 , 12 ]. For uncovering NPs encoded by these silent or cryptic genes, gene activation in the producer and heterologous expression in a well-studied host have proven reliable genetic approaches [ 13 , 14 ], which were also successfully used for gene identification in PRB-2 [ 15 ]. To enhance genetic manipulation, a pyrG deficient strain FK15 was created in a previous study [ 16 ].…”
Section: Introductionmentioning
confidence: 99%